2018
DOI: 10.1016/j.amjmed.2017.09.012
|View full text |Cite
|
Sign up to set email alerts
|

X + Y Scheduling Models in Internal Medicine Residency Programs: A National Survey of Program Directors' Perspectives

Abstract: AAIM is the largest academically focused specialty organization representing departments of internal medicine at medical schools and teaching hospitals in the United States and Canada. As a consortium of five organizations, AAIM represents department chairs and chiefs; clerkship, residency, and fellowship program directors; division chiefs; and academic and business administrators as well as other faculty and staff in departments of internal medicine and their divisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Second, a rapidly increasing number of IM residency programs in the USA have adopted the "X+Y" format to better balance the training environment between the inpatient and outpatient settings. Residents have dedicated ambulatory weeks ("Y weeks") where didactic sessions and administrative time occur prior to the start of the next inpatient block ("X weeks") [22]. This intervention was accessible to the trainees as preparatory learning during their more flexible administrative time prior to starting their HOS rotation; thus optimizing their time.…”
Section: Discussionmentioning
confidence: 99%
“…Second, a rapidly increasing number of IM residency programs in the USA have adopted the "X+Y" format to better balance the training environment between the inpatient and outpatient settings. Residents have dedicated ambulatory weeks ("Y weeks") where didactic sessions and administrative time occur prior to the start of the next inpatient block ("X weeks") [22]. This intervention was accessible to the trainees as preparatory learning during their more flexible administrative time prior to starting their HOS rotation; thus optimizing their time.…”
Section: Discussionmentioning
confidence: 99%
“…After a 2009 ACGME policy to improve resident continuity clinics and reduce the tension between inpatient and outpatient patient care responsibilities, 44% of PDs surveyed moved to an X + Y schedule model, most within a year. 26 Although the baseline rate of residency program schedule changes is unknown, we would have anticipated a similar rate of change to the new ACGME flexible work hours. Perhaps the difference reflects more compliance with restrictive policies than liberalizing policies.…”
Section: Discussionmentioning
confidence: 99%
“…24 X + Y scheduling, a model that schedules residents' inpatient or non-ambulatory rotations (BX^blocks) in discrete periods with alternating ambulatory or BY^blocks, is instituted specifically to decrease the conflict between inpatient and outpatient patient care responsibilities. 25,26 Several studies of X + Y scheduling have found this model to be associated with less care fragmentation, increased perception of clinic continuity among residents, and higher resident satisfaction. [27][28][29] Our study unearthed the association that primary care programs using the X + Y scheduling model were less likely to have a majority of their program graduates pursue primary care at the time of graduation.…”
Section: Discussionmentioning
confidence: 99%